Analisis Kehilangan Biaya Akibat Kemacetan Pada Kendaraan Pribadi (LCGC, SUV, dan MPV) di Ruas Jalan MH. Thamrin, Jakarta - Adita Utami; Fira Riska Syahrun; Asep Yayat Nurhidayat (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2023)
In this research, an analysis of Vehicle Operational Costs (BOK) is carried out for LCGC (Low Cost Green Car), MPV (Multi Purpose Vehicle) and SUV (Sport Utility Vehicle) types of vehicles on Jalan M.H. Thamrin. The purpose of this analysis is to determine performance on Jalan M.H. Thamrin, so there is a need for an analysis of Vehicle Operational Costs (BOK) that experience congestion and time delays when passing through the road using two methods, namely the LAPI ITB method and the PCI (Pacific Consulate International) method. time value which is the cost and time incurred due to congestion Time value analysis is based on the average income per person working in the Jalan M.H. Thamrin area by conducting interviews beforehand. reviewed based on observational BOK and free flow BOK H the results of the analysis of vehicle operating costs for free flow speed of 2,575.83 rupiah, 3,197.86 rupiah and 6,937.85 rupiah based on the LAPI ITB method, and BOK results based on the PCI method 2,492.34 rupiah, 3,169.41 rupiah and 7,857.50 rupiah. The results of the BOK analysis based on the LAPI ITB method were the highest for LCGC, MPV and SUV vehicles, respectively 4,098.88 rupiah, 5,146.55 rupiah and 12,405.66 rupiah with a travel speed of 13 km/hour. While the BOK results using the PCI method were the highest respectively at 5,444.36 rupiah, 7,108.68 rupiah and 18,010.69 rupiah at a speed of 13 km/hour. The results of the time value analysis are obtained based on the respondent's monthly income, which is 50,473 rupiah/hour. The total value of lost costs due to congestion is greatest when passing Jalan M.H. Thamrin for LCGC, MPV and SUV vehicles respectively 5,439,965 rupiah, 20,993,349 rupiah and 8,703,865 rupiah. Performance on Jalan M.H. Thamrin viewed from the value of the degree of saturation and service level with category D for the HI Roundabout direction to Medan Merdeka, while for the Medan Merdeka direction to HI Roundabout the service level category is D.